NCTzen Fandom Bandung Fanaticism on K-Pop Idol NCT - Nuha, Mohammad Nadwa Ulin; Wahyudin, Uud; Gemiharto, Ilham (Indonesian Journal of Economics, Social, and Humanities, 2023)
The development of technology, the emergence of various K-Pop groups that began to bewitch the Indonesian people. One of them, a boy group made by SM Entertainment, namely NCT. The NCTzen phenomenon increasingly shows that the movement of the Korean entertainment industry is mushrooming in Indonesian society. This study aims to find out the motives, experiences, and meanings of fanaticism for NCTzen Bandung in liking NCT. Fanaticism comes from the meaning of being a fan, where "ism" which is an understanding or view is combined into a fanatical view. The research method used is a qualitative method with a phenomenological approach. The resource person in this study looked at the research subject who is NCTzen Bandung and has good experience in supporting NCT. The results showed that the motive for favoring NCT was during the pandemic and needed entertainment content during activities at home. The various behaviors that NCTzen has in support of NCT are streaming, buying physical albums, voting, buying official merchandise, and watching NCT concerts. The meaning of being part of NCTzen is to be able to provide happiness and become a support system as long as NCTzen lives its daily life.